Daily field checking list by Walter Rosene, March 5, 1939 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene, Bob Walker and Samuel J. Hyde, March 5, 1939. Also notes the female Great Horned Owl was brooding three eggs. Plustek--flatbed